Brain susceptibility changes in neurologically asymptomatic pediatric patients with Wilson's disease: evaluation with quantitative susceptibility mapping. (November 2018) - Saracoglu, Sibel; Gumus, Kazim; Doganay, Selim; Koc, Gonca; Kacar Bayram, Ayse; Arslan, Duran; Gumus, Hakan
Background: Wilson's disease (WD) is a copper metabolism disorder that causes hepatolenticular degeneration. It is important to diagnose WD before central nervous system involvement. Purpose: To demonstrate the early susceptibility changes associated with the copper accumulation in the brain of neurologically asymptomatic pediatric patients with WD using quantitative susceptibility mapping (QSM). Material and Methods: Twelve patients with neurologically asymptomatic WD (mean age = 13.7 ± 3.3 years) and 14 age-matched controls were prospectively examined using a 1.5-T clinical scanner. Routine magnetic resonance (MR) sequences and a three-dimensional multi-echo spoiled gradient echo (GRE) sequence were used and QSM maps were reproduced. The quantitative susceptibility of corpus striatum, thalamus, substantia nigra, and pons were analyzed with the region of interest analysis on QSM maps. The susceptibility values of two groups were statistically compared using a two-sample t -test. Results: Conventional MR images of the patients and control group were similar. However increased magnetic susceptibility in the thalamus, pons and left posterior putamen were observed in the patients compared to the control group ( p < 0.05). Conclusion: We observed statistically increased susceptibility values in the brains of neurologically asymptomatic patients with WD although the conventional MR images were normal. This might be compatible with early brain impairment, before neurological symptoms occur.